Neglected culprit of nonlinear discharge characteristics in SF6: shielding effect induced by positive glow corona discharge. (22nd August 2019) - Wu, Zhicheng; Zhang, Qiaogen; Zhang, Lisong; Guo, Can; Du, Qiandong; Pang, Lei
Abstract: The discharge characteristics of SF6 dependent on gas pressure under extremely inhomogeneous electric fields are strongly nonlinear and must be carefully considered when optimizing gas-insulated equipment insulation design and defect detection. The main aim of this study was to determine the relationship between nonlinear breakdown characteristics and the pre-breakdown discharge mode transition. The breakdown model established by Niemeyer, as adapted under impulse voltage, was expanded. The images and the phase-resolved patterns of the pre-breakdown discharge as a function of gas pressure and applied voltage were analyzed to observe the relationship between them as per the spatial distribution of the spark paths. A universal model of the nonlinear breakdown phenomenon under steady-state voltage was established accordingly. Experimental results demonstrate the existence of a positive glow corona (PGC) discharge in the interval with the discontinuous breakdown voltage as well as significant interactions between the PGC discharge and leader discharge. The nonlinear characteristics can be attributed to the inception and quenching of the PGC discharge. The shielding effect induced by the PGC discharge is the neglected culprit of the strong nonlinear discharge characteristics under steady-state voltage. The nonmonotonic U–p curve in electronegative gases was also assessed in an effort to build a theoretical basis for the manufacture and condition monitoring of the gas-insulated equipment.